Closing the gender gap event: Mathieu Denis - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Mathieu Denis, Acting Executive Director of Science, ISSC at the Closing the gender gap in farming under climate change event held 19 March 2015 in Paris Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action